2010
DOI: 10.1007/s12272-010-1006-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia. It is characterized by extracellular deposition of a specific protein, beta-amyloid peptide fibrils, and is accompanied by extensive loss of neurons in the brains of affected individuals. Although the pathophysiologic mechanism is not fully established, inflammation appears to be involved. Neuroinflammation has been known to play a critical role in the pathogenesis of chronic neurodegenerative disease in general, and in AD in particular. Numerous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
225
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(234 citation statements)
references
References 200 publications
(164 reference statements)
4
225
0
5
Order By: Relevance
“…Some studies showed benefits of certain NSAIDs in the improvement of cognitive functions or delaying onset of AD. However, other studies showed no improvement (19). Intriguingly, while neuroinflammation, which accompanies development of AD, has been the primary reason for testing NSAIDs, several studies have suggested that the positive effects of this class of drugs are not related to inflammation (or A␤ processing, see below) (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed benefits of certain NSAIDs in the improvement of cognitive functions or delaying onset of AD. However, other studies showed no improvement (19). Intriguingly, while neuroinflammation, which accompanies development of AD, has been the primary reason for testing NSAIDs, several studies have suggested that the positive effects of this class of drugs are not related to inflammation (or A␤ processing, see below) (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that mitochondrial dysfunction [12,18,19] , metal accumulation [12,20,21] , hyperphosphorylated tau [22,23] , inflammation [24,25] , and β-amyloid (Aβ) accumulation [12,19] are the basic mechanisms underlying the induction of oxidative stress. Deficiency or destruction of components of the antioxidant system such as SOD in the mitochondria (Mn-SOD or SOD2) and cytosol (Cu-Zn-SOD or SOD1), [14,17,26] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent evidence suggests that 15d-PGJ2 may exert a protective effect on the CNS under pathological conditions, as well as antiviral effects (11). Thus, current research interests for the treatment of neurodegenerative diseases are focused primarily on PPARγ agonists such as 15d-PGJ2, which is being clinically evaluated for potential improvement of cognition (12,13). Recently, only minimal information is available regarding the effects of 15d-PGJ2 on HIV-1 Tat-induced cytotoxicity in the hippocampus, as well as the possible molecular pathways impinged upon by this process, despite of the intense research conducted to characterize the various biological activities of 15d-PGJ2.…”
Section: Human Immunodeficiency Virus-1 (Hiv-1) Infection Canmentioning
confidence: 99%